A pilot memory café for people with Learning Disabilities and memory difficulties. (9th June 2015) - Kiddle, Hannah; Drew, Neil; Crabbe, Paul; Wigmore, Jonathan
Abstract : Accessible summary: Memory cafés help people without learning disabilities who have dementia. We wanted to know whether memory cafés can help people with learning disabilities and memory problems. We ran a memory café for 12 weeks for people with learning disabilities. We watched how people got on in the café and how happy they looked. We asked people what they thought of the memory café. We also asked their carers. The people who came to the memory café said it helped. They seemed happier each week. Carers said that after the memory café people talked more, were more alert and did more activities at home. Summary: Memory cafés have been found to normalise experiences of dementia and provide access to an accepting social network. People with learning disabilities are at increased risk of developing dementia, but the possible benefits of attending a memory café are not known. This study evaluates a 12‐week pilot memory café for people with learning disabilities in terms of adaptations required and benefits of attending. Results indicate that affect levels significantly improved across the course of the café and that communication, interaction, alertness and participation in other activities improved outside the café. Future plans for attendance at memory cafés for people with learning disabilities are discussed.